2022
DOI: 10.3389/fendo.2022.969783
|View full text |Cite
|
Sign up to set email alerts
|

Association between the atherogenic index of plasma and new-onset non-alcoholic fatty liver disease in non-obese participants

Abstract: IntroductionNon-alcoholic fatty liver disease (NAFLD) in the non-obese population accounts for a large proportion of NAFLD. Atherogenic index of plasma (AIP, defined as the logarithm of the triglyceride/high-density lipoprotein cholesterol ratio.) can provide a stronger reflection of dyslipidemia and studies on the longitudinal association between AIP and NAFLD were limited in non-obese participants, especially in different BMI groups.MethodsWe performed a post-hoc analysis of data obtained from the Dryad data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Miao et al ( 8) using the same source data as ours investigated the relationship between Remnant lipoprotein cholesterol (RLP-C) and NAFLD, revealing that higher RLP-C levels were associated with an increased risk of NAFLD, with HRs for 1.6 and 1.3 in high and middle RLP-C groups. Li et al (7) involved 16,173 participants and use the atherogenic index of plasma (AIP) to predict NAFLD. Over a span of 5 years, 14.4% of the non-obese individuals developed NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miao et al ( 8) using the same source data as ours investigated the relationship between Remnant lipoprotein cholesterol (RLP-C) and NAFLD, revealing that higher RLP-C levels were associated with an increased risk of NAFLD, with HRs for 1.6 and 1.3 in high and middle RLP-C groups. Li et al (7) involved 16,173 participants and use the atherogenic index of plasma (AIP) to predict NAFLD. Over a span of 5 years, 14.4% of the non-obese individuals developed NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…As they often overlook the need for clinical evaluation for NAFLD and are likely to be overlooked in risk assessments for the condition, this population may pose greater challenges than obese individuals. Existing studies have proposed limited indices, including AIP (Atherogenic index of plasma) and RLP-C (Remnant lipoprotein cholesterol), as potential predictors for risk assessment in non-obese population (7,8). First proposed by Wang et al in a cross-sectional study involving 9,602 Chinese participants, the Zhejiang University (ZJU) Index proved to be a proficient tool for screening NAFLD (AUC=0.822) (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Min et al have found that individuals with abnormal glucose metabolism and higher AIP levels may have a greater risk of developing cardiovascular diseases [ 25 ]. In addition, higher levels of AIP have been found to be positively correlated with the risk of hypertension and non-alcoholic fatty liver disease, which is potentially influenced by the glucose metabolic states [ 26 28 ]. Interestingly, a cross-sectional study has demonstrated a strong association among elevated AIP levels, an increased risk of IR, and the onset of type 2 diabetes [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Min et al have found that individuals with abnormal glucose metabolism and higher AIP levels may have a greater risk of developing cardiovascular diseases (24). In addition, higher levels of AIP have been shown to be positively correlated with the risk of hypertension and non-alcoholic fatty liver disease, with this relationship potentially in uenced by the glucose metabolic states (25)(26)(27). Interestingly, a cross-sectional study has shown a strong association between elevated AIP levels and an increased risk of insulin resistance and the onset of type 2 diabetes (5).…”
Section: Subgroup Analysismentioning
confidence: 99%